Talaandig or Bukidnon? - Guasa, Jr., Pedro A. (The Archive; Vol 4 (1984): Publication Four: Studies on Philippine Minor Languages, 2025)
My paper this afternoon consists of two parts: first, an indorsement and/or recommendation for the recognition/acceptance of Talaandig or TInalaandig as one of the minor languages of the Philippines and second, a socio-linguistic discussion of the languages in the province of Bukidnon. [...] There are two native languages in Bukidnon—the Talaandig, which includes the Bukidnon and the Umayamnon, and the Manobo, which includes the Tigwahanon and the Matigsalug. Other languages brought in by migrants are Cebuano, Hiligaynon, Waray, Ilocano, Ivatan and Maranao.